A new cancer on the block: Tuberous sclerosis-associated renal cell carcinoma. (January 2023) - Cui, Helen; Verrill, Clare; Sullivan, Mark
Purpose: The purpose of this article is to present the first reported case of a renal tumour classified as tuberous sclerosis complex-associated renal cell carcinoma in the UK and discuss its clinical implications. Case report: A female, aged 65 years, with tuberous sclerosis complex was found on surveillance imaging to have interval growth of multiple right renal tumours up to 19 mm. Right partial nephrectomy was performed. Histology showed multiple tiny angiomyolipomas and a 20 mm tumour classified as tuberous sclerosis complex-associated renal cell carcinoma. These tumour cells showed abundant clear cytoplasm with a branched elongated arrangement encircled in dense smooth muscle stroma. Literature review: Renal cell carcinoma in patients with tuberous sclerosis complex is rare, occurring in approximately 4% of cases. Tuberous sclerosis complex-associated renal cell carcinoma is a relatively new histological entity, having previously been described as clear cell or chromophobe-like, with only one published case series from the USA. These tumours have three histological entities which are distinct from all other renal cell carcinoma classifications. Based on case series, tuberous sclerosis complex-associated renal cell carcinoma tends to occur more often in females, present at a younger age, have multiple tumours, and tend to show an indolent course, although metastases have been reported. Learning points: Patients with tuberous sclerosis complex can develop renal cell carcinoma, though the risk is thought to be no higher than for sporadic renal cell carcinoma. Given the limited literature, more evidence is required to help predict the future behaviour of these tumours. Level of evidence: 5